On the genus Cosmopelma Simon, 1889 (Araneae, Barychelidae) - Mori, Andre; Bertani, Rogerio (Zootaxa, 2016)
Among neotropical mygalomorph spider families, Barychelidae is one of the most neglected in taxonomic studies. Most genera have never been revised and only the original descriptions are available. Herein, one of these more obscure genera, Cosmopelma Simon, 1892, with two described species in Brazil and Venezuela, is revised. The type species C. decoratum Simon, 1889 is redescribed, and the male is described for first time. A new species, C. ceplac sp. nov., is described, and new occurrences are presented. Additionally, C. dentatum Fischel, 1927, whose holotype is lost, is considered a nomen dubium. Cosmopelma is an endemic genus, known only from the state of Bahia in northeastern Brazil.